i-Youth Pro: Be vocal, be human, be you / Zarinatun Ilyani Abdul Rahman - Abdul Rahman, Zarinatun Ilyani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
Acknowledging this quote, Akademi Pengajian Bahasa (APB) UiTM Perak Branch, Students Representative Council and HEP UiTM Perak Branch had organized an International Youth Humanitarian Programme (i-YoutH Pro) on April 19 - 20, 2019. This programme was a collaboration with Syria Care and Global Peace Mission (GPM) Malaysia; the NGOs which are actively involved in humanitarian mission. i-YoutH Pro 2019 with its tagline 'Be Vo-cal, Be Human, Be You' was held to create an awareness regarding hu-manitarian issues at local and international levels among its participants. Several activities were conducted as platforms for the participants to voice out their opinions and views regarding this issue and to help those in need through a humanitarian donation drive.